2015
DOI: 10.5056/jnm14093
|View full text |Cite
|
Sign up to set email alerts
|

The Resveratrol-induced Relaxation of Cholecystokinin Octapeptide- or KCl-induced Tension in Male Guinea Pig Gallbladder Strips Is Mediated Through L-type Ca2+ Channels

Abstract: Background/Aims Resveratrol (3,5,4′-trihydroxystilbene) is a polyphenolic compound (stilbene) and a phytoalexin. The purpose of this study was to determine the mechanism which mediated the resveratrol-induced relaxation of cholecystokinin octapeptide- or KCl-induced tension in male guinea pig gallbladder strips. Methods Gallbladder strips were prepared and suspended in in vitro chambers filled with Krebs-Henseleit solution. The strips were attached to force displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Park et al, described resveratrol [ 67 ] to be a potent antagonist of cAMP PDEs (including PDE1-4) that inhibits these enzymes directly in a concentration-dependent manner. Kline and Karpinski [ 68 ] observed resveratrol’s ability to induce NOS-3 in direct and indirect manners through AMPK, SIRT1 and nuclear factor erythroid 2-related factor 2 pathways. Additionally, they noticed that resveratrol acts directly on VSMCs by blocking the l -type calcium channel resulting in limitation of intracellular Ca2+ release.…”
Section: Vascular Reactivitymentioning
confidence: 99%
“…Park et al, described resveratrol [ 67 ] to be a potent antagonist of cAMP PDEs (including PDE1-4) that inhibits these enzymes directly in a concentration-dependent manner. Kline and Karpinski [ 68 ] observed resveratrol’s ability to induce NOS-3 in direct and indirect manners through AMPK, SIRT1 and nuclear factor erythroid 2-related factor 2 pathways. Additionally, they noticed that resveratrol acts directly on VSMCs by blocking the l -type calcium channel resulting in limitation of intracellular Ca2+ release.…”
Section: Vascular Reactivitymentioning
confidence: 99%
“…Fernandez-Morales et al observed similar effects at nanomolar concentrations of resveratrol [13]. Kline and Karpiński's [14] study showed that resveratrol also depends on nonreceptor vasorelaxant mechanisms. In the assessment of the potential impact of cyclic nucleotides in resveratrolinduced hyporeactiveness, 8Br-cGMP, a low molecular weight analogue with high tissue penetration, was used in two concentrations: 0.01 mM/l and 0.1 mM/l (Experiment No.…”
Section: Discussionmentioning
confidence: 83%
“…The 'functional reserve' of resveratrol (additional decrease of vessel reactivity in the presence of A7-hydrochloride) suggests that resveratrol may not only induce vasorelaxation via the cyclic guanosine monophosphate (cGMP)-dependent pathways. Kline and Karpinski (36) described the ability of resveratrol to induce NOS-3 in direct and indirect manners through the 5' adenosine monophosphate-activated protein kinase (AMPK), SIRT1 and nuclear factor erythroid 2-related factor 2 pathways; but it is also stated that resveratrol acts directly on VSMCs by blocking the L-type calcium channel and inhibiting intracellular Ca 2+ release.…”
Section: Discussionmentioning
confidence: 99%